2020
DOI: 10.1002/csc2.20399
|View full text |Cite
|
Sign up to set email alerts
|

Wild Lathyrus species as a great source of resistance for introgression into cultivated grass pea (Lathyrus sativus L.) against broomrape weeds (Orobanche crenata Forsk. and Orobanche foetida Poir.)

Abstract: Broomrape weeds (Orobanche spp.) are root holoparasitic plants that cause serious damage to a range of legume crops in the Mediterranean and sub-Saharan African regions. Grain yield of cultivated species of grass pea (Lathyrus sativus L.) is almost negligible at the highest infection severity of Orobanche. Crop wild relatives (CWRs) have emerged as a novel source for many traits in diverse crops. Lathyrus is one of the largest genera with more than 160 species. In the present study, we screened 285 accessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Parasitism Index was positively correlated with EON and EODW, which reflects the severe negative effect of O. crenata parasitism on lentil growth and seed production. Similar results were reported in previous studies performed on faba bean (Abbes et al 2011;Trabelsi et al 2015;Trabelsi et al 2016), lentil (Ennami et al 2017), chickpea (Nefzi et al 2016) and grass pea (Abdallah et al 2020).…”
Section: Field Evaluationsupporting
confidence: 92%
See 2 more Smart Citations
“…Parasitism Index was positively correlated with EON and EODW, which reflects the severe negative effect of O. crenata parasitism on lentil growth and seed production. Similar results were reported in previous studies performed on faba bean (Abbes et al 2011;Trabelsi et al 2015;Trabelsi et al 2016), lentil (Ennami et al 2017), chickpea (Nefzi et al 2016) and grass pea (Abdallah et al 2020).…”
Section: Field Evaluationsupporting
confidence: 92%
“…Such resistance was expressed by the lowest shoot and root dry weight reduction and a low number of total O. crenata shoots and tubercules. similar results were reported in previous studies performed on faba bean and lentil (Ennami et al 2017;Abdallah et al 2020) who reported a large variation in infestation intensity under pots conditions and field trials.…”
Section: Pot Experimentssupporting
confidence: 91%
See 1 more Smart Citation
“…Recourses available in genebanks have been used in a number of studies, for example Abdallah et al (2020) obtained 285 accessions, representing 13 Lathyrus (grass pea) species, from The International Center for Agricultural Research in the Dry Areas (ICARDA) and showed that wild Lathyrus species have higher resistance to broomrape weeds (Orobanche spp. ), a root holoparasitic plant that causes significant damage to legume crops (Abdallah et al, 2021). Dida et al (2021) obtained 52 finger millet accessions, including landraces, wild lines and hybrids between wild and cultivated genotypes, from the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) and Genetic Resources Research Institute (GeRRI) genebanks and found that wild accessions were more resistant to blast disease, caused by the Magnaporthe grisea fungus, in comparison to the cultivated accessions (Dida et al, 2021).…”
Section: Ex-situ Resourcesmentioning
confidence: 99%
“…Although CWR have been relatively neglected for decades [ 15 ], their potential was highlighted by Vavilov, and their use in breeding has been increasing since the 1980s [ 16 ]. The use of CWR is widespread and well-established for crops such as barley [ 17 ], potato [ 18 ], wheat [ 19 , 20 , 21 , 22 ] and rice [ 23 , 24 , 25 ] and developing for others such as alfalfa [ 26 ], carrot [ 27 ], chickpea [ 28 ], eggplant [ 29 , 30 ], finger millet [ 31 ], grass pea [ 32 ] and sorghum [ 33 , 34 ]. The starting point for use is viable hybridization between the crop and a wild relative.…”
Section: Introductionmentioning
confidence: 99%